Recent Trade Policies and An Approach to Further Reform in the Baltics, Russia, and Other Countries of the Former Soviet Union - Leidy, Michael (IMF Working Papers; Working Paper, 1996)
This paper reviews the extent to which the Fund's trade policy advice to the Baltic countries, Russia and other countries of the Former Soviet Union has been implemented. It broadly traces the evolution of trade policies, emphasizing the period from mid-1993 through end-1995, attempting to identify some of the factors affecting uneven progress in trade reform. Based on insights from the public choice literature on endogenous policy theory, the paper makes recommendations for refining Fund advice with a view to facilitating future progress on the trade-policy front.